Analysis of Greenhouse Gas and Pollutant Emission Reduction in Ukraine and European Union Countries - Stepan Mysak; Stepan Shapoval; Marta Martynyak-Andrushko (Energy Engineering and Control Systems)
Following the European Green Deal, which aims to develop a closed-loop economy and reduce emissions of pollutants, Ukraine is also implementing it in its plans. Therefore, this paper analyzes and compares the reduction of CO2, NOx and SO2 emissions by the European Community countries and Ukraine. Actual data on achievements in reducing emissions of the specified substances and the plans of the countries under study have been analyzed and compared. Based on the elaboration of the energy and climate plans of the countries of the European Union and Ukraine, graph-analytical dependencies have been built, based on which the actual achievements since 1990 by the countries in reducing emissions of greenhouse gases and pollutants have been analyzed. Also the plans for these data represented by the countries by 2050 have been compared.